Sistem Kontrol Frekuensi Optimal Pada Pembangkit Hibrid Wind-Diesel Dengan Imperialist Competitive Algorithm - Muhammad Ruswandi Djalal; Andi Imran; Herlambang Setiadi (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
Frequency load arrangement on wind-diesel hybrid power plants (PLTH) becomes a very important thing in order to support the performance of the plant. One method of setting the load frequency is to use additional controllers such as Proportional Integral Derivative (PID). The use of PID also has its own problems, such as adjusting the value of unoptimal gain. In practice the PID gain is observed by trial-error, making it difficult to obtain the optimal value of the PID. In this research, we proposed an intelligent method of Imperialist Competitive Algorithm (ICA) in finding the optimal value of PID. The ICA is a smart method inspired by the competition in power struggles. ICA works based on the objective function, which minimizes Integral Time Absolute Error (ITAE). From the results of ICA optimization obtained value Kp = 63.1087, Ki = 43.2682, Kd = 9.6038. Response system, among others, for the settling time of 5.8 and overshoot of -9.098e-05 to 1.111e-09 pu which is the smallest settling time and overshoot value.